(untitled) (Journal of Environmental Microbiology and Toxicology, 2024)
This study examined the postharvest spoilage of cucumber (Cucumis sativus L.) caused by fungal pathogens in retail outlets in Dutse Metropolis, Jigawa State, Nigeria. Twelve cucumber samples were collected from three locations: Sabuwar Kasuwa, Hakimi Street, and Yan Tifa, with four samples per site. Fungal isolates were identified using morphological characteristics. The predominant fungi were Aspergillus flavus, Aspergillus niger, and Aspergillus ustus, as well as the yeast Zygosaccharomyces bailii, which was the most frequently isolated species. Pathogenicity tests confirmed that all isolates could cause rot, with Aspergillus ustus being the most virulent, resulting in a 47 mm diameter of rot and 25.5% weight loss. These results highlight the potential public health risks associated with fungal contamination, particularly the production of harmful mycotoxins. The study emphasizes the importance of adopting improved handling and storage practices to minimize food spoilage and ensure food safety. Regular monitoring of fungal contamination in retail outlets is recommended to protect consumer health.